Negotiating 'ideal worker' and intensive mothering ideologies: Australian mothers' emotional geographies during their commutes. (24th March 2022) - Rodriguez Castro, Laura; Brady, Michelle; Cook, Kay
ABSTRACT: Individualized, maternalist and marketized discourses of childcare are pervasive in Australia as they are in other liberal welfare states. Responsibility is overwhelmingly placed on mothers to carry out most childcare work themselves or to arrange informal or paid childcare. One of the key tasks for most employed mothers is transporting children alongside their commuting journeys. In this context we used mapping/graphic elicitation interviews with 45 Australian employed mothers to explore their commuting experiences through the lens of emotional geographies. Our findings reveal that mothers' experiences of their commutes were shaped by negotiations with intensive mothering and 'ideal worker' ideologies during this journey resulting in emotions of guilt, shame and stress. The spatial and temporal organization of childcare, and incompatibilities between their commuting transport needs and the organization of public transport and parking, tended to amplify these tensions. Through an emotional geographies lens we complicate linear understandings of commuting and mainstream transport and planning work, while calling for more attention to the affective and relational dimensions of mothers' everyday geographies of care and paid work.